2019
DOI: 10.1021/acsami.9b18961
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional N-Doped Carbon Nanotube Frameworks on Ni Foam Derived from a Metal–Organic Framework as a Bifunctional Electrocatalyst for Overall Water Splitting

Abstract: Rational design of bifunctional, high-performance, and stable non-noble metal-based electrocatalysts for hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) is of great importance and challenging for the realization of overall water splitting. Metal–organic frameworks (MOFs) have been intensively studied as pyrolyzing precursors to prepare electrocatalysts. However, the aggregation of powder and the low conductivity of polymer binders have limited the applications of powder electrocatalysts. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(49 citation statements)
references
References 64 publications
0
49
0
Order By: Relevance
“…Besides, it is critical that improving MOF conductivity to enhance their intrinsic catalytic activity because of their low electronic conductivity and poor mass permeability. One effective strategy is to fabricate their derivatives through high temperature pyrolysis or chemical conversions, such as metal oxides or hydroxides, carbon‐based derivatives, and composite materials . Although these derivatives exhibit improved electrocatalytic performance compared with the pristine MOFs precursors, during the pyrolysis, the intrinsic structure of MOFs has been destroyed, simultaneously, these expensive organic ligands have been decomposed, severely hampering their practically large‐scale application.…”
Section: Methodsmentioning
confidence: 99%
“…Besides, it is critical that improving MOF conductivity to enhance their intrinsic catalytic activity because of their low electronic conductivity and poor mass permeability. One effective strategy is to fabricate their derivatives through high temperature pyrolysis or chemical conversions, such as metal oxides or hydroxides, carbon‐based derivatives, and composite materials . Although these derivatives exhibit improved electrocatalytic performance compared with the pristine MOFs precursors, during the pyrolysis, the intrinsic structure of MOFs has been destroyed, simultaneously, these expensive organic ligands have been decomposed, severely hampering their practically large‐scale application.…”
Section: Methodsmentioning
confidence: 99%
“…Compared with the traditional MOF‐polyhedrons derived densely packed electrocatalysts, the MPZ‐CC@CNT exhibited a greatly enhanced electrochemical active surface area, which was ascribed to the minimized “prohibited zones” for this multidimensional ordered configuration. Similarly, ZIF‐67 nanosheets arrays can also grow on the surface of Ni foam, [ 192 ] which was converted into 3D N‐doped CNT frameworks with Co–N–C active sites, acting as effective electrocatalyst for overall water splitting. In another research, Selomulya and coworkers fabricated PBA nanotubular arrays on the surface of Ni foam through an anion exchange process (Figure 12e,f).…”
Section: Mofs Derivatives For Oxygen Electrocatalysismentioning
confidence: 99%
“…Moreover, pyrolyzing organometallics onto high surface area carbon has shown to improve OER performance . It has also been demonstrated that doping heteroatoms such as nitrogen, phosphorus, and boron within carbon supports can contribute to the overall improved electrocatalytic activity by modulating the electronic structure of the Ir center . Herein, we prepared a series of electrocatalysts by pyrolyzing Ir organometallics (Figure ) in the presence of a Norit® activated carbon, and subsequently assessed the OER/CER activity by introducing heteroatom doping based on nitrogen,phosphorus, and chlorine composition of the organometallic.…”
Section: Figurementioning
confidence: 99%
“…[38,39,40] It has also been demonstrated that doping heteroatoms such as nitrogen, phosphorus, and boron within carbon supports can contribute to the overall improved electrocatalytic activity by modulating the electronic structure of the Ir center. [41,42] Herein, we prepared a series of electrocatalysts by pyrolyzing Ir organometallics ( Figure 1) in the presence of a Norit® activated carbon, and subsequently assessed the OER/CER activity by introducing heteroatom doping based on nitrogen,phosphorus, and chlorine composition of the organometallic. The electrocatalysts reported in the present study are cost-effective, requiring only 2-6 wt% Ir loading (based on calculations; Table 1), and are prepared using a highly scalable process.…”
mentioning
confidence: 99%